A semantic sense-and-respond approach to managing IT-enabled buyer-supplier relationships: an action research study. (2017) - Kaul, Mala; Feng, Jing Betty; Mathiassen, Lars
As a reflection of the strategic importance of buyer-supplier relationships in supply chains, information sharing and knowledge exchange have been found to positively impact coordination, transparency, and perception of trust between buyers and sellers. However, our knowledge about IT as an enabler in buyer-seller relationships is limited. Against this backdrop, we examined how a large retailer, BuildSmart, adapted and leveraged a portal to help 'listen to the voice of their suppliers'. Through a collaborative action research project, we developed a semantic sense-and-respond approach to design and implement mechanisms that allowed BuildSmart to continuously sense how suppliers experienced their portal and how to generally improve their supplier relationships. As a result, we present a model for managing IT-enabled buyer-supplier relationships and demonstrate how conceptual modeling can be combined with sense-and-respond thinking to support IT-enabled process management.